O X da questão: o fenômeno Xuxa e a construção das crianças com o X - Sinval, Maria Julianna Formiga Moura (2010)
The research then has to verify the proposed Xuxa phenomenon. The focus is the study of the image of Xuxa, during the program Xuxa, as the predominant item in capturing the look of the spectator. The choice of this figure takes into account the identification of the mass audience with his image. Xuxa inspires devotion and worship, and many children are thought to be a magician. She became part of the childhood of a whole generation of Brazilians and by 1990 it was possible to speak of a "generation Xuxa, a group that grew up during the era of Xuxa. Based on the discussion as to where is the essence of the success of the "Queen of baixinhos" and what the background that supported his image because Xuxa emerged in the media as a sex symbol training and soon took on the role of idol children in this sense the intention of the research is to show how the image is transformed into a spectacular appearance made by the media and how that image affects the cultural imaginary. Thus, there was a background scenery of Xuxa, a biographical summary of the presenter, where several issues were mythical figure attached to the hero. In addition, treated the issues of fame in contemporary issues of children's consumption, as well as the main themes included in this process: Television and Magazine. Therefore, the methodology consisted of a theoretical basis, selection of scenes during the Xuxa Xuxa, articles published in the journal and reflective and critical analysis of selected content. Through literature, this fascination that the media image of Xuxa has on viewers, has been examined in the light of various scholars of communication, such as Edgar Morin, Regis Debray, Muniz Sodré, Ciro Marcondes Filho, Malena Contreras and the notion of iconofagia proposal by Norval Baitello. In dialogue with and support the authors found that the image produced by the TV capture through its superficial content and search more and more to capture the imagination as a place for commercial exploitation, encouraging children a mentally passive activity. Therefore, the child becomes a spectator of events, preventing the authentic emotions. Image dualistic Xuxa projected on television is the perfect support to hold the projection of the dual character of the goddess Venus, Urania (heavenly) and Pandemic (popular). Thus the media retains the attention of viewers, adults and children, and engage in the light of Venus, which glows with the beauty impeccable. And that's too much light that makes this a "lack of communication